ANALISIS MAKNA UPACARA TEPUNG TAWAR DALAM PERNIKAHAN ADAT MELAYU RIAU - Maini, Maini; Perdamean, Ahmad Sahat (Universitas Tanjungpura, 2023)
ABSTRACTTepung Tawar is one of the Malay tribal traditions that are still practiced in Malay society today. The purpose of this study was to analyze the meaning Tepung Tawar in Malay marriages. The analysis is focused on: (1) the ceremony Tepung Tawar, (2) the symbol Tepung Tawar and (3) the meaning of the Flour. This study uses descriptive qualitative methods with data collection through interviews with the secretary of traditional institutions, recording video and audio as observation material. In analyzing the meaning of the symbol Tepung Tawar in Malay marriages, Charles Sanders Peirce's semiotic theory is used. The results of this study relate to the Malay tribal community. There are many symbols contained in the ceremony Tepung Tawar, namely yellow rice, washing rice, bertih, potpourri, henna, sedingin leaves, setawar leaves, jun-juang leaves, double deer leaves, ati-ati leaves, fragrant powder, water (fresh flour) and a hand wash bowl. Each symbol contained in the ceremony Tepung Tawar in the marriage of the Malay tribe has a certain meaning. Keywords: Semiotics; Tradition; Tepung Tawar ABSTRAKTepung Tawar adalah salah satu Tradisi suku Melayu yang masih dilakukan di masyarakat Melayu hingga saat ini. Tujuan dari penelitian ini adalah untuk menganalisis makna Tepung Tawar dalam pernikahan suku Melayu. Analisis di fokuskan pada: (1) upacara Tepung Tawar, (2) simbol Tepung Tawar dan (3) makna Tepung Tawar. Penelitian ini menggunakan metode kualitatif deskriftif dengan pengumpulan data melalui wawancara dengan sekretaris lembaga adat, merekam video dan audio sebagai bahan observasi. Dalam menganalisis makna dari simbol Tepung Tawar dalam pernikahan suku Melayu menggunakan teori semiotika Charles Sanders Peirce. Hasil penelitian ini berkaitan dengan masyaraat suku Melayu. Ada banyak simbol yang terkandung dalam upacara Tepung Tawar, yaitu beras kuning, beras basuh, bertih, bunga rampai, inai, daun sedingin, daun setawar, daun jun-juang, daun ganda rusa, daun ati-ati, bedak harum, air Tepung Tawar dan mangkok cuci tangan. Setiap simbol yang terkandung dalam upacara Tepung Tawar dalam pernikahan suku melayu mempunyai makna tertentu. Kata kunci: Semiotik; tradisi; Tepung Tawar